Clinicopathologic features and prognostic significance of CD30 expression in de novo diffuse large B-cell lymphoma (DLBCL): results in a homogeneous series from a single institution. (2nd January 2020) - Salas, María Queralt; Climent, Fina; Tapia, Gustavo; DomingoDomènech, Eva; Mercadal, Santiago; Oliveira, Ana Carla; Aguilera, Carmen; Olga, García; Moreno Velázquez, Miriam; Andrade-Campos, Marcio; Encuentra, Maite; Fernández de Sevilla, Alberto; et al.
Abstract: Introduction: The present study evaluates CD30 expression by immunohistochemistry (IHQ) in 216 patients with de novo DLBCL. Methods: CD30 expression was assessed retrospectively in all cases by IHQ. More than >0% and >20% of CD30 expression in the malignant cells were used as a cut-off for positivity. Survival was analysed in 176 patients treated with R-CHOP/R-CHOP-like regimens. Results: CD30 expression >0% was found in 66 (31%) patients, and >20% in 41 (19%). Younger patients <60 years ( p  = 0.03), good performance status ( p  = 0.04), and non-GCB subtype ( p  = 0.004) correlated with CD30 expression. No significant differences were found in overall survival and progression-free survival (PFS), although there was a trend towards better PFS in CD30-positive patients ( p  = 0.07). Among 7 patients with Epstein-Barr virus (EBV)-positive-DLBCL, CD30 was expressed in 71%, and 2-year PFS significantly inferior compared with CD30-positive EBV-negative-DLBCL patients ( p =  0.01). Conclusion: CD30 is expressed in 30% of DLBCL patients, in whom targeted therapy with an anti-CD30 monoclonal antibody could be explored. CD30 is expressed more frequently younger patients, with better performance status and in the non-GCB subtype and its expression trends towards a better PFS. No significant differences regarding characteristics at diagnosis or prognosis were found between groups with different cut-off for positivity.